2017
DOI: 10.3899/jrheum.170384
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Outcome of Psoriatic Arthritis Patients with Hyperuricemia

Abstract: HUC is common in patients with PsA, especially in those with longer disease duration and obesity. Proper control of HUC and metabolic diseases may play a preventive role in improving PsA outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
5
19
0
3
Order By: Relevance
“…Three other studies used a list of comorbidities to evaluate the impact of the number of reported comorbidities on PROs in PsA patients [14,88,95]. One of these studies, a prospective observational study with more than 600 patients with PsA, found that the presence of at least three comorbidities significantly worsened a patient's quality of life, as assessed with the SF- Abou-Raya/2014 [18] No data regarding the impact of comorbidity on PROs 2 Aguiar/2013 [20] No data regarding the impact of comorbidity on PROs 3 Aguiar/2013 [19] No data regarding the impact of comorbidity on PROs 4 Akhtari/2018 [21] No data regarding the impact of comorbidity on PROs 5 Aljohani/2017 [22] No data regarding the impact of comorbidity on PROs 6 Arancibia/2014 [24] No data regarding the impact of comorbidity on PROs 7 Arancibia/2015 [23] No data regarding the impact of comorbidity on PROs 8 Bandinelli/2009 [25] No numerical data provided 9 Batkaeva/2018 [26] No data regarding the impact of comorbidity on PROs [14]. A second study, a small prospective study, used the Functional Comorbidity Index (FCI) to corroborate that an increase in the number of comorbidities was significantly associated with moderate-severe work disability (OR 2.31, 95% CI 1.19-4.50).…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies used a list of comorbidities to evaluate the impact of the number of reported comorbidities on PROs in PsA patients [14,88,95]. One of these studies, a prospective observational study with more than 600 patients with PsA, found that the presence of at least three comorbidities significantly worsened a patient's quality of life, as assessed with the SF- Abou-Raya/2014 [18] No data regarding the impact of comorbidity on PROs 2 Aguiar/2013 [20] No data regarding the impact of comorbidity on PROs 3 Aguiar/2013 [19] No data regarding the impact of comorbidity on PROs 4 Akhtari/2018 [21] No data regarding the impact of comorbidity on PROs 5 Aljohani/2017 [22] No data regarding the impact of comorbidity on PROs 6 Arancibia/2014 [24] No data regarding the impact of comorbidity on PROs 7 Arancibia/2015 [23] No data regarding the impact of comorbidity on PROs 8 Bandinelli/2009 [25] No numerical data provided 9 Batkaeva/2018 [26] No data regarding the impact of comorbidity on PROs [14]. A second study, a small prospective study, used the Functional Comorbidity Index (FCI) to corroborate that an increase in the number of comorbidities was significantly associated with moderate-severe work disability (OR 2.31, 95% CI 1.19-4.50).…”
Section: Resultsmentioning
confidence: 99%
“…Other diagnostic tools include laboratory tests and imaging. Although no specific laboratory test is available for PsA, it is often characterized by negative results for rheumatoid factor and anti-citrullinated peptides, with possible laboratory abnormalities, including hyperuricemia, elevated C-reactive protein, and prolonged erythrocyte sedimentation rate [50,51]. Radiographs allow visualization of PsA-associated features (e.g., new bone formation), and magnetic resonance imaging provides visualization of soft tissue, facilitating the detection of enthesitis and spondylitis [52][53][54][55].…”
Section: Diagnosis Of Psamentioning
confidence: 99%
“…These include an increased level of uric acid, alcohol abuse, hypertension, the use of antihypertensives, increased body mass index (BMI) and familial history of gout (5). In addition, it has been reported that gout may be associated with persistent psoriasis especially in male patients and in those with other causes of hyperuricemia (6). Gout arthritis is most commonly seen in the metatarsophalangeal joint.…”
mentioning
confidence: 99%